Nursing Ethical Leadership Questionnaire: An Improved Measure of Ethical Leadership - Naveed Tariq; Kashif Amin (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study aims to provide a tool to measure nurse Ethical Leadership competencies. In this study, the researcher tested a novel questionnaire to measure ethical leadership. The study examines how ethical leadership affects employee voice. Although these studies are meant to examine the new questionnaire's criterion-related validity, the results assist answer issues concerning ethical leadership. Ethical leadership contributes somewhat but significantly to employee voice behavior. This research employed qualitative and quantitative methodologies. A systematic questionnaire was employed for data collection. The study's primary results were drawn from the analyzed tables. This study's findings imply a relationship between ethical leadership and employee voice.